Carbon material and preparation method thereof, water-based conductive coating and carbon-coated aluminum foil
By alkizing the carbon material and surface modification, the problem of poor adhesion of aqueous conductive coatings on the surface of aluminum foil is solved, and the conductivity is improved, and the resistance is reduced by nearly 50%.
Patent Information
- Application Number
- CN202311692987.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-07
- Filing Date
- 2023-12-11
- Publication Date
- 2025-02-18
AI Technical Summary
The poor adhesion of existing water-based conductive coatings on the surface of aluminum foil leads to limited conductivity and difficult to effectively improve.
By alkizing and surface modification of the carbon material, the hydroxyl groups that can be grafted on the surface of the carbon material are added, and low-polar small molecule substances are used as surface modifiers. The modified carbon material has oil-friendly rolling Coordinate the high oil absorption value characteristics of carbon materials, destroy the oil film and improve adhesion.
The adhesion of aqueous conductive coating on the surface of aluminum foil is achieved, which can increase the filling amount of carbon material, thereby improving the conductive properties of the coating, and the resistance is reduced by nearly 50%.
Smart Images

Figure CN119463536A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a carbon material and a preparation method thereof, a water-based conductive coating and a carbon-coated aluminum foil. Background Art
[0002] Water-based conductive coating is a coating with bonding and conductive effects. The carbon coating formed after film formation is applied to the surface of the positive electrode current collector of lithium-ion batteries to reduce the internal resistance of the battery, prevent the positive electrode active material from falling off and protect the current collector. Therefore, the adhesion to the current collector aluminum foil, the peel strength to the positive electrode active material, the conductivity after film formation and the resistance to the electrolyte are the core properties of water-based conductive coating.
[0003] like Figure 1 As shown, in terms of adhesion performance, the polar groups such as carboxyl groups in the resin component of the water-based conductive coating easily interact with the hydroxyl groups on the surface of the current collector aluminum foil, and have good adhesion performance in theory. However, due to the cold rolling process of the current collector aluminum foil, a large amount of rolling oil is easily left on the surface. These rolling oils have very low polarity and form a molecular-level isolation oil film between the carbon coating and the current collector aluminum foil, which blocks the contact between the polar groups of the coating and the aluminum foil, seriously affecting the adhesion performance. The commonly used method at present is to temporarily change the polarity of the residual rolling oil or reduce the residual amount by corona or baking the substrate to improve the adhesion of the carbon coating, but the effect is limited, and it is not effective for heavily oil-stained aluminum foil or current collector aluminum foil with oil spots.
[0004] In addition, as the source of the conductive properties of water-based conductive coatings, the filling amount of carbon materials is an important parameter indicator. Since carbon materials do not have adhesion to aluminum foil, the more filling amount, the better the conductivity but the worse the adhesion, which limits the further improvement of the conductive properties of carbon coatings; therefore, how to overcome the above-mentioned technical problems and defects has become a key issue that needs to be solved. Summary of the invention
[0005] In view of the problem that the existing water-based conductive coating has poor adhesion on the surface of aluminum foil, the present invention provides a carbon material and a preparation method, a water-based conductive coating and a carbon-coated aluminum foil.
[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0007] The first aspect of the present invention provides a method for preparing a carbon material, comprising the following steps:
[0008] Alcoholization treatment of carbon material: water, alcoholization agent and carbon material are mixed evenly, and alcoholization treatment is performed at 150° C.-180° C. for 3-5 hours to obtain alcoholized carbon material;
[0009] Surface modification of carbon material: The alcoholized carbon material is modified by using a surface modifier, wherein the surface modifier includes one or more of hydroxyalkanoates or phosphates to obtain a modified carbon material.
[0010] Optionally, the operation of "uniformly mixing water, alcoholizing agent and carbon material" includes: uniformly mixing 50-75 parts of water, 26-47 parts of alcoholizing agent and 1-3 parts of carbon material by weight.
[0011] Optionally, in the operation of "alcoholization treatment of carbon materials", it is included that: the carbon material includes one or more of carbon black, graphite, graphene, and carbon nanotubes; the alcoholization agent includes one or more of nitric acid, phosphoric acid, perchloric acid, and sulfuric acid.
[0012] Optionally, the "carbon material surface modification" operation includes: dissolving 0.3 to 0.8 parts of the surface modifier in a first solvent by weight, then adding 4.5 to 7 parts of the alcoholized carbon material, stirring and ultrasonically treating for 5 to 20 minutes, transferring to a reactor, and reacting at 120°C to 160°C for 8 to 12 hours.
[0013] Optionally, in the operation of "carbon material surface modification", the first solvent includes one or more of carbon tetrachloride, toluene, xylene, butyl ester, ethylene glycol monobutyl ether, propylene glycol methyl ether, propylene glycol butyl ether, propylene glycol methyl ether acetate, dipropylene glycol methyl ether and dipropylene glycol methyl ether acetate.
[0014] Optionally, the hydroxyalkanoic acid ester substances include one or more of 16-hydroxy-hexadecanoic acid methyl ester, 16-hydroxy-hexadecanoic acid butyl ester, 12-hydroxy-dodecanoic acid ethyl ester, 3-hydroxyhexadecanoic acid methyl ester, hydroxytetradecanoic acid methyl ester, and hydroxytetradecanoic acid butyl ester; the phosphate esters include one or more of diphenyl phosphate, ditolyl phosphate, dipentyl phosphate, dibutyl phosphate, dimethyl phosphate, diethyl phosphate, and dipropyl phosphate.
[0015] A second aspect of the present invention provides a carbon material prepared by the above-mentioned method for preparing the carbon material.
[0016] The third aspect of the present invention provides a water-based conductive coating, which comprises, by weight, 35 to 75 parts of water, 15 to 20 parts of a second solvent, 15 to 30 parts of a resin and 4.5 to 8 parts of the above-mentioned carbon material.
[0017] Optionally, the second solvent includes one or more of ethanol, ethylene glycol monobutyl ether, and ethylene glycol; the resin includes one or more of acrylic resin, epoxy resin, polyester resin, and polyurethane resin.
[0018] A fourth aspect of the present invention provides a carbon-coated aluminum foil, comprising a current collector and a coating layer, wherein the coating layer is coated on at least one surface of the current collector, and the coating layer is formed by coating the above-mentioned aqueous conductive coating on at least one surface of the current collector.
[0019] According to the preparation method of the carbon material provided by the present invention, the present invention first performs alcoholization treatment on the carbon material to increase the hydroxyl groups on the surface of the carbon material available for grafting; then the alcoholized carbon material is surface modified; the specific method is: in a solvent phase, through high temperature and high pressure conditions, the carbon material is modified using a surface modifier; the surface modifier is a low-polarity small molecule substance, and since the main component of the residual rolling oil is low-polarity substances such as alkanoates, the modified carbon material has a certain affinity for rolling oil, and its application in water-based conductive coatings can cooperate with the high oil absorption value of the carbon material, open the "blockade" of the oil film, and allow polar groups such as carboxyl groups in the coating resin to contact the substrate to generate a force, thereby achieving improved adhesion; based on the improvement in adhesion, in the formulation design process of the water-based conductive coating, the filling amount of the carbon material can be increased to achieve improved conductive properties of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a rendering of the carbon material of the present invention before treatment;
[0021] Figure 2 This is a diagram showing the effect of the carbon material after treatment of the present invention;
[0022] Figure 3 This is a comparison diagram of the adhesion of the carbon coating prepared by carbon material modification and the untreated carbon coating on the surface of the heavy oil-contaminated current collector aluminum foil;
[0023] The reference numerals in the drawings of the specification are as follows:
[0024] 1-Carbon coating; 11-Active groups in the resin; 12-Groups grafted on the surface of the carbon material; 2-Positive electrode current collector; 21-Active groups in the substrate; 3-Residual rolling oil. DETAILED DESCRIPTION
[0025] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0027] In one embodiment, the first aspect of the present invention provides a method for preparing a carbon material, comprising the following steps:
[0028] Alcoholization treatment of carbon material: water, alcoholization agent and carbon material are mixed evenly, and alcoholization treatment is performed at 150° C.-180° C. for 3-5 hours to obtain alcoholized carbon material;
[0029] Surface modification of carbon material: The alcoholized carbon material is modified by using a surface modifier, wherein the surface modifier includes one or more of hydroxyalkanoates or phosphates to obtain a modified carbon material.
[0030] Specifically, the alcoholization treatment of the carbon material includes the pretreatment of the carbon material, and the pretreatment of the carbon material includes the following steps: ultrasonically cleaning the carbon material in a cleaning agent to remove impurities on the surface of the carbon material, filtering, washing, and drying to obtain a clean carbon material; the mass ratio of the carbon material to the cleaning agent is 1-10:90-99.
[0031] In a preferred embodiment, the mass ratio of the carbon material to the cleaning agent is 3-8:92-97; for example, any mass ratio of 1:99; 2:98; 3:97; 4:96; 5:95; 6:94; 7:93; 8:92; 9:91 or 10:90.
[0032] Specifically, 5 parts of carbon material were placed in an ultrasonic cleaning device, and 95 parts of a cleaning agent were added and cleaned for 10 minutes to remove impurities on the surface of the carbon material. Then, an appropriate filter cloth was selected for suction filtration, and the mixture was washed with water and dried in a vacuum drying oven at 50°C.
[0033] In one embodiment, the cleaning agent is one or more of butanone, acetone, ethyl acetate, ethanol and butyl acetate.
[0034] The cleaning agent can remove impurities on the surface of the carbon material, and the clean carbon material can be obtained through filtering, washing and drying.
[0035] Specifically, in the alcoholization process of the carbon material, the water is deionized water or distilled water; the specific process is: the water, alcoholization agent and carbon material are mixed evenly and then transferred to a reactor, and alcoholization treatment is performed at 150°C-180°C for 3-5h, the carbon material after alcoholization treatment is taken out, centrifuged and washed, and vacuum dried in an environment of 40°C-60°C to obtain the alcoholized carbon material.
[0036] In a preferred embodiment, the reactor is a high-pressure reactor, and further, the high-pressure reactor is a high-pressure reactor lined with polytetrafluoroethylene.
[0037] In a preferred embodiment, the temperature for the alcoholization treatment of water, alcoholization agent and carbon material is 160° C., and the time for the alcoholization treatment is 4 hours.
[0038] In a preferred embodiment, the carbon material after alcoholization treatment is vacuum dried at a temperature of 50°C. In one embodiment, the surface modifier includes one or more of hydroxyalkanoates or phosphates, and the carbon material is modified using low-polarity small molecular substances such as hydroxyl long-chain alkanoates and phosphates. Since the main component of the residual rolling oil is low-polarity substances such as alkanoates, the modified carbon material has a certain affinity for rolling oil. Applying it in water-based conductive coatings can cooperate with the high oil absorption value of the carbon material, open the "blockade" of the oil film, and make the polar groups such as carboxyl groups in the coating resin contact with the substrate to generate a force, thereby improving the adhesion; based on the improvement of adhesion, in the formulation design process of the water-based conductive coating, the filling amount of the carbon material can be increased to improve the conductive performance of the coating.
[0039] like Figure 1 As shown, the polar groups such as carboxyl groups in the resin component of the water-based conductive coating can easily interact with the hydroxyl groups on the surface of the current collector aluminum foil, and theoretically have good adhesion performance. However, it is limited by the cold rolling process of the current collector aluminum foil, which leads to a large amount of rolling oil remaining on the surface. The rolling oil has very low polarity and forms a molecular-level isolation oil film between the carbon coating and the current collector aluminum foil, which blocks the contact between the polar groups of the coating and the aluminum foil, seriously affecting the adhesion performance.
[0040] Figure 2 The figure is a rendering of the film formation of the water-based conductive coating of the present invention on the surface of the current collector; the present invention first performs alcoholization treatment on the carbon material to increase the hydroxyl groups grafted on the surface of the carbon material; then the surface of the alcoholized carbon material is modified; the specific method is: in a solvent phase, the carbon material is modified by using a surface modifier under high temperature and high pressure conditions; the surface modifier is a low-polarity small molecule substance, and since the main component of the residual rolling oil is low-polarity substances such as alkanoates, the modified carbon material has a certain affinity for rolling oil, and its application in water-based conductive coatings can cooperate with the high oil absorption value of the carbon material, open the "blockade" of the oil film, and allow polar groups such as carboxyl groups in the coating resin to contact the substrate to generate a force, thereby achieving improved adhesion.
[0041] In one embodiment, the operation of "uniformly mixing water, alcoholizing agent and carbon material" includes: uniformly mixing 50-75 parts of water, 26-47 parts of alcoholizing agent and 1-3 parts of carbon material by weight.
[0042] In a preferred embodiment, the water is 60-65 parts, for example, any point value among 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts or 75 parts, or a range value composed of any two points.
[0043] In a preferred embodiment, the alcoholizing agent is 30 to 40 parts, for example, any value among 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts or 47 parts, or a range value consisting of any two values.
[0044] In a preferred embodiment, the carbon material is 1.5 to 2.5 parts, for example, any one of 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts or 3.0 parts, or a range value consisting of any two points.
[0045] The type and amount of alcohol used for the activation treatment of carbon materials, as well as the temperature and time conditions of the treatment process, must be matched experimentally, because a strong alcoholization process will cause the carbon material structure to decrease and affect the conductivity, while an overly mild alcoholization process cannot produce enough active sites for reaction; within the range of 50 to 75 parts of water, 26 to 47 parts of alcoholizing agent and 1 to 3 parts of carbon material and alcoholization at 150°C to 180°C for 3 to 5 hours, it will not affect the conductivity of the carbon material, but will also increase the number of hydroxyl groups available for grafting on the surface of the carbon material, thereby facilitating the subsequent modification of the carbon material.
[0046] In one embodiment, in the operation of "alcoholization treatment of carbon materials", it includes: the carbon material includes one or more of carbon black, graphite, graphene, and carbon nanotubes; the alcoholization agent includes one or more of nitric acid, phosphoric acid, perchloric acid, and sulfuric acid.
[0047] Specifically, the carbon black includes conductive carbon black, and the conductive carbon black includes acetylene black and furnace black.
[0048] The graphite includes, but is not limited to, one or more of natural graphite, artificial graphite, amorphous carbon, carbon-coated graphite, graphite-coated graphite, and resin-coated graphite. The natural graphite may be scaly graphite, flaky graphite, soil graphite, and / or graphite particles obtained by using these graphites as raw materials and subjecting them to spheroidization, densification, and the like. The artificial graphite may be obtained by graphitizing organic substances such as coal tar pitch, coal-based heavy crude oil, atmospheric residue, petroleum-based heavy crude oil, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural polymers, polyphenylene sulfide, polyphenylene ether, furfuryl alcohol resin, phenolic resin, and imide resin at high temperatures.
[0049] Specifically, nitric acid, phosphoric acid, perchloric acid, and sulfuric acid can provide graftable hydroxyl groups on the surface of the carbon material, facilitating the subsequent modification of the carbon material.
[0050] In one embodiment, the "carbon material surface modification" operation includes: dissolving 0.3 to 0.8 parts of the surface modifier in a first solvent by weight, then adding 4.5 to 7 parts of the alcoholized carbon material, stirring and ultrasonically treating for 5 to 20 minutes, transferring to a reactor, and reacting at 120°C to 160°C for 8 to 12 hours.
[0051] In a preferred embodiment, the surface modifier is 0.4 to 0.7 parts, for example, any one of 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts or 0.8 parts, or a range consisting of any two of the values.
[0052] In a preferred embodiment, the alcoholized carbon material is 5 to 6 parts, for example, 4.5 parts, 4.6 parts, 4.7 parts, 4.8 parts, 4.9 parts, 5.0 parts, 5.1 parts, 5.2 parts, 5.3 parts, 5.4 parts, 5.5 parts, 5.6 parts, 5.7 parts, 5.8 parts, 5.9 parts, 6.0 parts, 6.1 parts, 6.2 parts, 6.3 parts, 6.4 parts, 6.5 parts, 6.6 parts, 6.7 parts, 6.8 parts, 6.9 parts or 7.0 parts, any one of the values or a range consisting of any two values.
[0053] Specifically, the process of modifying the alcoholized carbon material with the surface modifier is as follows: dissolve the surface modifier in the first solvent, then add the alcoholized carbon material, stir at 600 rpm and ultrasonically treat for 10 minutes, transfer to a reactor, react at 120°C to 160°C for 8 to 12 hours, take out, filter and wash with chloroform, and dry in a vacuum drying oven at 80°C to obtain a modified carbon material.
[0054] In a preferred embodiment, the heating temperature is 130°C to 150°C, for example, any value among 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C, 130°C, 131°C, 132°C, 133°C, 134°C, 135°C, 136°C, 137°C, 138°C, 139°C, 140°C, 141°C, 142°C, 143°C, 144°C, 145°C, 146°C, 147°C, 148°C, 149°C, 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, or a range consisting of any two value points.
[0055] In a preferred embodiment, the reaction time is 9-11 h; for example, any point value among 8 h, 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h or 12 h, or a range value consisting of any two point values.
[0056] In one embodiment, in the operation of "carbon material surface modification", the first solvent includes one or more of carbon tetrachloride, toluene, xylene, butyl ester, ethylene glycol monobutyl ether, propylene glycol methyl ether, propylene glycol butyl ether, propylene glycol methyl ether acetate, dipropylene glycol methyl ether and dipropylene glycol methyl ether acetate.
[0057] In one embodiment, the hydroxyalkanoic acid ester substances include one or more of 16-hydroxy-hexadecanoic acid methyl ester, 16-hydroxy-hexadecanoic acid butyl ester, 12-hydroxy-dodecanoic acid ethyl ester, 3-hydroxyhexadecanoic acid methyl ester, hydroxytetradecanoic acid methyl ester, and hydroxytetradecanoic acid butyl ester; the phosphate esters include one or more of diphenyl phosphate, ditolyl phosphate, dipentyl phosphate, dibutyl phosphate, dimethyl phosphate, diethyl phosphate, and dipropyl phosphate.
[0058] Specifically, 16-hydroxy-hexadecanoic acid methyl ester, 16-hydroxy-hexadecanoic acid butyl ester, 12-hydroxy-dodecanoic acid ethyl ester, 3-hydroxyhexadecanoic acid methyl ester, hydroxytetradecanoic acid methyl ester, and hydroxytetradecanoic acid butyl ester are hydroxy long-chain alkanoic acid esters; diphenyl phosphate, ditolyl phosphate, dipentyl phosphate, dibutyl phosphate, dimethyl phosphate, diethyl phosphate, and dipropyl phosphate are low-polarity small molecular substances of the phosphate ester class; the carbon material is modified by using hydroxy long-chain alkanoic acid esters and low-polarity small molecular substances of the phosphate ester class; since the main components of the residual rolling oil are low-polar substances such as alkanoic acid esters, the modified carbon material has a certain affinity for rolling oil, and its application in water-based conductive coatings can cooperate with the high oil absorption value characteristics of the carbon material, open the "blockade" of the oil film, and allow polar groups such as carboxyl groups in the coating resin to contact the substrate to generate a force, thereby achieving improved adhesion; based on the improvement of adhesion, in the formulation design process of the water-based conductive coating, the filling amount of the carbon material can be increased to achieve improved conductive properties of the coating.
[0059] A second aspect of the present invention provides a carbon material prepared by the above-mentioned method for preparing the carbon material.
[0060] The modified carbon material in the present application has a certain affinity for rolling oil. When used in water-based conductive coatings, it can cooperate with the high oil absorption characteristics of the carbon material to open the "blockade" of the oil film so that polar groups such as carboxyl groups in the coating resin can contact the substrate to generate a force, thereby achieving improved adhesion.
[0061] The third aspect of the present invention provides a water-based conductive coating, which includes, by weight, 35 to 75 parts of water, 15 to 20 parts of a second solvent, 15 to 30 parts of a resin and 4.5 to 8 parts of the above-mentioned carbon material. After mixing evenly, a sand mill is used to disperse the mixture to a fineness of 10 to 25 to obtain a water-based conductive coating.
[0062] Preferably, the fineness of the coating is 10-25; the viscosity is 30-1000 mPa·S, and the solid content of the coating is 5-15%.
[0063] In a preferred embodiment, the water is 40 to 70 parts, for example, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74 or 75 parts, any one of the values or a range consisting of any two of the values.
[0064] In a preferred embodiment, the second solvent is 16-18 parts, for example, any value among 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, or a range consisting of any two values.
[0065] In a preferred embodiment, the resin is 20 to 25 parts, for example, any point value among 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts, or a range value consisting of any two point values.
[0066] In a preferred embodiment, the carbon material is 5 to 8 parts, for example, any value among 4.5 parts, 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts or 8.0 parts, or a range value consisting of any two values.
[0067] This application applies the modified carbon material to water-based conductive coatings. Based on the principle of similar compatibility and the high oil absorption value of the carbon material, the oil film is destroyed, so that groups such as carboxyl groups in the coating resin can contact the substrate to improve adhesion.
[0068] Based on the improvement of adhesion, the amount of carbon material can be increased in the formulation design of water-based conductive coatings to improve the conductivity of the coating. For example, the carbon material filling amount is increased from 55% to 70%, and the resistance is reduced by nearly 50%.
[0069] In one embodiment, the second solvent includes one or more of ethanol, ethylene glycol monobutyl ether, and ethylene glycol; the resin includes one or more of acrylic resin, epoxy resin, polyester resin, and polyurethane resin.
[0070] A fourth aspect of the present invention provides a carbon-coated aluminum foil, comprising a current collector and a coating layer, wherein the coating layer is coated on at least one surface of the current collector, and the coating layer is formed by coating the above-mentioned aqueous conductive coating on at least one surface of the current collector.
[0071] The coating layer on the surface of the carbon-coated aluminum foil of the present application is formed by coating a water-based conductive coating on at least one surface of the current collector. The water-based conductive coating of the present application uses a modified carbon material. The modified carbon material is applied to the water-based conductive coating. According to the principle of similar compatibility, the high oil absorption value of the carbon material is coordinated to destroy the oil film, so that the carboxyl group and other groups in the coating resin can contact the substrate to achieve improved adhesion. Based on the improvement of adhesion, in the formulation design process of the water-based conductive coating, the filling amount of the carbon material can be increased to achieve improved coating conductivity. For example, the carbon material filling amount is increased from 55% to 70%, and the resistance is reduced by nearly 50%; it can not only reduce the substrate processing cost, but also improve the construction adaptability of the water-based conductive coating, and further increase the carbon material filling amount to reduce resistance, which is very meaningful for improving the overall performance of lithium-ion batteries.
[0072] In one embodiment, the coating layer of the carbon-coated aluminum foil has a thickness of 0.3-2 μm.
[0073] In a preferred embodiment, the coating layer thickness of the carbon-coated aluminum foil is 0.5-1.5 μm, for example, any point value among 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, and 2.0 μm, or a range value consisting of any two point values.
[0074] The present invention is further described below by way of examples.
[0075] Embodiment 1:
[0076] 1. Alcoholization treatment of carbon materials:
[0077] 1) 5 parts of carbon material were ultrasonically cleaned in 95 parts of butanone for 10 minutes to remove impurities on the surface of the carbon material, and then filtered with appropriate filter cloth, washed with deionized water and dried in a vacuum drying oven at 50°C;
[0078] 2) 57 parts of deionized water, 40 parts of dilute nitric acid, 1 part of phosphoric acid, and 2 parts of acetylene black were mixed in sequence, stirred evenly, and then transferred to a high-pressure reactor lined with polytetrafluoroethylene, and alcoholized for 4 hours at 160°C. The mixture was taken out by centrifugation and washed with deionized water, and vacuum dried at 50°C to obtain an alcoholized carbon material.
[0079] 2. Surface modification of carbon materials
[0080] First, 0.78 parts of 12-hydroxy-dodecanoic acid ethyl ester was dissolved in toluene, and then 7 parts of alcoholized carbon material was added. After stirring at 600 rpm and ultrasonic treatment for 10 minutes, it was transferred to a reactor and reacted at 120°C for 10 hours. The mixture was taken out, filtered, washed with chloroform, and dried in a vacuum drying oven at 80°C to obtain an alkanoate-modified carbon material.
[0081] 3. Preparation of positive electrode water-based carbon-coated aluminum foil:
[0082] 48.89 parts of deionized water, 20 parts of solvent, 25 parts of resin, and 6.11 parts of alkanoate-modified carbon material were mixed in order, and then dispersed to a fineness of 15 using a sand mill to obtain a water-based conductive coating with a carbon material filling amount of 55%. The coating was coated on both sides of the current collector aluminum foil and baked in a hot air oven at 125°C for 30 seconds to obtain a carbon-coated aluminum foil with a single-side coating thickness of 0.5 μm, marked as S1.
[0083] Example 2
[0084] Example 2 is used to illustrate a carbon material and preparation method, water-based conductive coating and carbon-coated aluminum foil disclosed in the present invention, including most of the operating steps in Example 1, except that:
[0085] Preparation of positive electrode water-based carbon-coated aluminum foil:
[0086] 51.12 parts of deionized water, 20 parts of solvent, 22.22 parts of resin, and 6.66 parts of alkanoate-modified carbon material were mixed in order, and then dispersed to a fineness of 15 using a sand mill to obtain a water-based conductive coating with a carbon material filling amount of 60%. The coating was coated on both sides of the current collector aluminum foil and baked in a hot air oven at 125°C for 30 seconds to obtain a carbon-coated aluminum foil with a single-side coating thickness of 0.5 μm, marked as S2.
[0087] Example 3
[0088] Example 3 is used to illustrate a carbon material and preparation method, water-based conductive coating and carbon-coated aluminum foil disclosed in the present invention, including most of the operating steps in Example 1, except that:
[0089] Preparation of positive electrode water-based carbon-coated aluminum foil:
[0090] 53.34 parts of deionized water, 20 parts of solvent, 19.44 parts of resin, and 7.22 parts of alkanoate-modified carbon material were mixed in order, and then dispersed to a fineness of 15 using a sand mill to obtain a water-based conductive coating with a carbon material filling amount of 65%. The coating was coated on both sides of the current collector aluminum foil and baked in a hot air oven at 125°C for 30 seconds to obtain a carbon-coated aluminum foil with a single-side coating thickness of 0.5 μm, marked as S3.
[0091] Example 4
[0092] Example 4 is used to illustrate a carbon material and preparation method, water-based conductive coating and carbon-coated aluminum foil disclosed in the present invention, including most of the operating steps in Example 1, except that:
[0093] Preparation of positive electrode water-based carbon-coated aluminum foil:
[0094] 55.55 parts of deionized water, 20 parts of solvent, 16.67 parts of resin, and 7.78 parts of alkanoate-modified carbon material were mixed in order, and then dispersed to a fineness of 15 using a sand mill to obtain a water-based conductive coating with a carbon material filling amount of 70%. The coating was coated on both sides of the current collector aluminum foil and baked in a hot air oven at 125°C for 30 seconds to obtain a carbon-coated aluminum foil with a single-side coating thickness of 0.5 μm, marked as S4.
[0095] Comparative Example 1
[0096] Comparative Example 1 is used to illustrate a carbon material and preparation method, a water-based conductive coating and a carbon-coated aluminum foil disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0097] Without alcoholization treatment of the carbon material, a water-based conductive coating with a carbon material filling amount of 55% was prepared, and after baking, a carbon-coated aluminum foil was obtained, which was marked as X1.
[0098] Comparative Example 2
[0099] Comparative Example 2 is used to illustrate a carbon material and preparation method, a water-based conductive coating and a carbon-coated aluminum foil disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0100] Without alcoholization treatment of the carbon material, a water-based conductive coating with a carbon material filling amount of 70% was prepared, and after baking, a carbon-coated aluminum foil was obtained, which was marked as X2.
[0101] Comparative Example 3
[0102] Comparative Example 3 is used to illustrate a carbon material and preparation method, a water-based conductive coating and a carbon-coated aluminum foil disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0103] Without modifying the surface of the carbon material, a water-based conductive coating with a carbon material filling amount of 55% was prepared, and after baking, a carbon-coated aluminum foil was obtained, which was marked as X3.
[0104] Comparative Example 4
[0105] Comparative Example 4 is used to illustrate a carbon material and preparation method, a water-based conductive coating and a carbon-coated aluminum foil disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0106] Without modifying the surface of the carbon material, a water-based conductive coating with a carbon material filling amount of 70% was prepared, and after baking, a carbon-coated aluminum foil was obtained, which was marked as X4.
[0107] Comparative Example 5
[0108] Comparative Example 5 is used to illustrate a carbon material and preparation method, a water-based conductive coating and a carbon-coated aluminum foil disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0109] Without performing carbon material treatment, a water-based conductive coating with a carbon material filling amount of 55% was prepared, and after baking, a carbon-coated aluminum foil was obtained, which was marked as X5.
[0110] Comparative Example 6
[0111] Comparative Example 6 is used to illustrate a carbon material and preparation method, a water-based conductive coating and a carbon-coated aluminum foil disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0112] Without performing carbon material treatment, a water-based conductive coating with a carbon material filling amount of 70% was prepared, and after baking, a carbon-coated aluminum foil was obtained, which was marked as X6.
[0113] Performance Test:
[0114] (I) Adhesion test:
[0115] The carbon-coated aluminum foils prepared in Examples 1-4 and Comparative Examples 1-6 were peeled off using 3M tape to evaluate the degree of peeling;
[0116] Test method: Place the coating side of the carbon-coated aluminum foil upwards, stick 3M tape on the coating, flatten the 3M tape on the coating with your fingers to remove the bubbles between the 3M tape and the coating, so that the 3M tape can adhere to the coating as tightly as possible. Pull the 3M tape vertically upwards from the bottom, and record the degree of coating shedding.
[0117] (ii) Conductivity test:
[0118] The carbon-coated aluminum foils prepared in Examples 1-4 and Comparative Examples 1-6 were tested for resistance respectively;
[0119] The test equipment is a diaphragm resistance test system, Chuanyuan Technology TT-ACCF-G2A; the test pressure is 23Mpa, and the pressure holding time is 5 seconds. Three values are tested for each carbon-coated aluminum foil, and the results are averaged.
[0120] The test results obtained in Examples 1 to 4 and Comparative Examples 1 to 6 are entered in Table 1.
[0121] Table 1
[0122] Carbon coating Adhesion Resistance (mΩ) S1 OK 3.59 S2 OK 3.11 S3 OK 2.44 S4 OK 1.82 X1 Small amount 3.42 X2 Large 1.80 X3 All Drop 3.49 X4 All Drop 1.82 X5 All Drop 3.38 X6 All Drop 1.80
[0123] Some adhesion test results are as follows: Figure 3 As shown; from left to right they are X5, X6, S4;
[0124] From the test results in Table 1, it can be seen that Examples 1-4 of the present invention use long-chain alkanoate or phosphate small molecule materials with a structure similar to the residual rolling oil of the substrate as grafts to achieve surface modification of the carbon material through high-pressure solvent thermal reaction. The modified carbon material is applied to water-based conductive coatings. According to the principle of similar compatibility, the high oil absorption value of the carbon material is coordinated to destroy the oil film, so that the carboxyl groups in the coating resin can contact the substrate to improve the adhesion. Figure 1 and Figure 2 To analyze the adhesion improvement mechanism, Figure 3 The adhesion of the coating before (X6) and after (S4) carbon material treatment is shown, and it can be seen that the adhesion is significantly improved;
[0125] Based on the improvement of adhesion, the amount of carbon material can be increased in the formulation design of water-based conductive coatings to improve the conductivity of the coating. For example, the carbon material filling amount is increased from 55% to 70%, and the resistance is reduced by nearly 50%.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon material, characterized in that: The following steps are involved: Alcoholization treatment of carbon material: water, alcoholization agent and carbon material are mixed evenly, and alcoholization treatment is performed at 150° C.-180° C. for 3-5 hours to obtain alcoholized carbon material; Surface modification of carbon material: using a surface modifier to modify the alcoholized carbon material, wherein the surface modifier includes one or more of hydroxyalkanoates or phosphates to obtain a modified carbon material.
2. The method for preparing the carbon material according to claim 1, characterized in that: The operation of "mixing water, alcoholizing agent and carbon material uniformly" includes: mixing 50-75 parts of water, 26-47 parts of alcoholizing agent and 1-3 parts of carbon material uniformly by weight.
3. The method for preparing the carbon material according to claim 1, characterized in that: In the operation of "alcoholization treatment of carbon materials", it includes: the carbon material includes one or more of carbon black, graphite, graphene, and carbon nanotubes; the alcoholization agent includes one or more of nitric acid, phosphoric acid, perchloric acid, and sulfuric acid.
4. The method for preparing the carbon material according to claim 1, characterized in that: The "carbon material surface modification" operation includes: dissolving 0.3 to 0.8 parts of the surface modifier in a first solvent by weight, then adding 4.5 to 7 parts of the alcoholized carbon material, stirring and ultrasonically treating for 5 to 20 minutes, transferring to a reactor, and reacting at 120° C. to 160° C. for 8 to 12 hours.
5. The method for preparing the carbon material according to claim 4, characterized in that: In the operation of "carbon material surface modification", the first solvent includes one or more of carbon tetrachloride, toluene, xylene, butyl ester, ethylene glycol monobutyl ether, propylene glycol methyl ether, propylene glycol butyl ether, propylene glycol methyl ether acetate, dipropylene glycol methyl ether and dipropylene glycol methyl ether acetate.
6. The method for preparing the carbon material according to claim 1, characterized in that: The hydroxyalkanoic acid ester substances include one or more of 16-hydroxy-hexadecanoic acid methyl ester, 16-hydroxy-hexadecanoic acid butyl ester, 12-hydroxy-dodecanoic acid ethyl ester, 3-hydroxyhexadecanoic acid methyl ester, hydroxytetradecanoic acid methyl ester, and hydroxytetradecanoic acid butyl ester; the phosphate esters include one or more of diphenyl phosphate, ditolyl phosphate, dipentyl phosphate, dibutyl phosphate, dimethyl phosphate, diethyl phosphate, and dipropyl phosphate.
7. A carbon material, characterized in that: The carbon material is prepared by the method for preparing the carbon material according to any one of claims 1 to 6.
8. A water-based conductive coating, characterized in that: By weight, it comprises 35 to 75 parts of water, 15 to 20 parts of a second solvent, 15 to 30 parts of a resin and 4.5 to 8 parts of the carbon material according to claim 7.
9. The water-based conductive coating according to claim 8, characterized in that: The second solvent includes one or more of ethanol, ethylene glycol monobutyl ether, and ethylene glycol; the resin includes one or more of acrylic resin, epoxy resin, polyester resin, and polyurethane resin.
10. A carbon-coated aluminum foil, characterized in that: The invention comprises a current collector and a coating layer, wherein the coating layer is coated on at least one surface of the current collector, and the coating layer is formed by coating the aqueous conductive coating according to any one of claims 8 to 9 on at least one surface of the current collector.
Citation Information
Cited By
Carbon material and preparation method therefor, water-based conductive coating, and carbon-coated aluminum foil
EP4825922A1
Carbon material and preparation method therefor, water-based conductive coating, and carbon-coated aluminum foil
WO2025123927A1